Reviews of recent publications (Studies in 20th & 21st Century Literature, 1999)
Lucile C. Charlebois. Understanding Camilo José Cela Reviewed by Jessica A. Folkart Rainer Nägele. Echoes of Translation: Reading Between Texts Reviewed by Carol Jacobs Siegfried Mews (ed.). A Bertolt Brecht Reference Companion Reviewed by Horst Lange Suzanne Nalbantian. Æsthetic Autobiography: From Life to Art in Marcel Proust, James Joyce, Virginia Woolf and Anaïs Nin Reviewed by Laurence M. Porter
Keywords: Lucile C. Charlebois; Understanding Camilo José Cela; Jessica A. Folkart; Rainer Nägele; Echoes of Translation: Reading Between Texts; Carol Jacobs; Siegfried Mews; A Bertolt Brecht Reference Companion; Horst Lange; Suzanne Nalbantian; Æsthetic Autobiography: From Life to Art in Marcel Proust James Joyce Virginia Woolf and Anaïs Nin; Laurence M. Porter